Effect of Age on Sexual Behaviour, Scrotal Circumference and Scrotal Surface Temperature in Sahiwal Bulls (Indian Journal of Animal Production and Management, 2024)
Age of the bull influences the sexual  behaviour and quality of semen. The present study  was conducted to find out the age window at which  the bull shows best reproductive performance.  Fifteen Sahiwal bulls were selected and classified  into three age groups (n=5, in each group) - G1(2- 3.5), G2 (>3.5-8) and G3 (>8-12) years. The sexual  behaviour was recorded at the time of semen  collection by CCTV camera at 15 days interval.  Scrotal circumference (by scrotal tape) and scrotal  surface temperature (by IRT) were also taken at  monthly interval. The data so obtained in the  experiment was subjected to statistical analysis by  one-way analysis of variance (ANOVA) using SPSS  software version 26.0 to draw scientific  interferences. The results revealed that the mean  value of scrotal circumference was significantly  (p3.5-8) group except for the time to enter arena  from preparation site and total number of  mountings. Therefore, it can be concluded from this  study that sexual behaviour is influenced by age  and adult (middle) aged bulls performed better as  compared to young and old groups.
Keywords: age; Sahiwal bulls; scrotal circumference; scrotal surface temperature; sexual behaviour